Study on the Physical Characteristics and Phenolic Antioxidants of Kelulut Honey from Central Java Village, Galang Village, and Parit Baru Village, West Kalimantan - Aschida, Feliks Chu Junloi; Dewi, Yohana Sutiknyawati Kusuma; Maherawati, Maherawati (FoodTech: Jurnal Teknologi Pangan, 2025)
This study aims to evaluate the physicochemical characteristics and antioxidant activity of stingless bee honey (kelulut honey) from three different locations in West Kalimantan: Desa Jawa Tengah, Desa Galang, and Desa Parit Baru. The study analyzed key parameters, including color, viscosity, total dissolved solids, and phenolic antioxidant activity using spectrophotometric methods. The results showed that honey from Desa Galang exhibited the highest antioxidant activity and total dissolved solids, suggesting its superior biological potential. Conversely, honey from Desa Parit Baru demonstrated the lowest viscosity, indicating a thinner consistency. This research concludes that geographical differences influence honey quality, as demonstrated by the variations in antioxidant and physicochemical properties among the samples.